2008
DOI: 10.2987/5559.1
|View full text |Cite
|
Sign up to set email alerts
|

Community Aerial Mosquito Control and Naled Exposure

Abstract: In October 2004, the Florida Department of Health (FLDOH) and the Centers for Disease Control and Prevention (CDC) assessed human exposure to ultra-low volume (ULV) aerial application of naled. Teams administered activity questionnaires regarding pesticide exposure and obtained baseline urine samples to quantify prespray naled metabolite levels. Following the spray event, participants were asked to collect postspray urine specimens within 12 h of the spray event and at 8-h intervals for up to 40 h. Upon comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…73 Human health risks associated with ultra-low volume organophosphate or synthetic pyrethroid use appear negligible, largely because the timing of application and low volume of pesticide used result in minimal human exposure. 74,75 …”
Section: Treatment and Preventionmentioning
confidence: 99%
“…73 Human health risks associated with ultra-low volume organophosphate or synthetic pyrethroid use appear negligible, largely because the timing of application and low volume of pesticide used result in minimal human exposure. 74,75 …”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Kutz and Strassman [57] and Duprey et al [58] demonstrated that aerial spraying of naled did not result in increased levels of organophosphate urinary metabolites in humans. Other studies have shown that there were no significant increases in asthma related visits to hospitals after ULV applications of pyrethroid insecticides [56–60].…”
Section: Resultsmentioning
confidence: 99%
“…A decade after the initial response to WNV, several quantitative human-health and ecological risk assessments have been conducted to estimate the magnitude of risks associated with the insecticides ( Davis, 2007 ; Davis, Peterson & Macedo, 2007 ; Gosselin et al, 2008 ; Macedo, Peterson & Davis, 2007 ; New York City Department of Health, 2005 ; Peterson, Macedo & Davis, 2006 ; Schleier III, 2008 ; Schleier III et al, 2009a ; Schleier III et al, 2008a ; Schleier III et al, 2009b ; Schleier III et al, 2008b ; Suffolk County, 2006 ; United States Environmental Protection Agency, 2005b ; United States Environmental Protection Agency, 2005c ; United States Environmental Protection Agency, 2005d ; United States Environmental Protection Agency, 2006a ; United States Environmental Protection Agency, 2006b ; United States Environmental Protection Agency, 2006c ; Valcke, Gosselin & Belleville, 2008 ). Also, there have been epidemiology and biomonitoring studies measuring the health effects after potential exposure to mosquito adulticides ( Currier et al, 2005 ; Duprey et al, 2008 ; Karpati et al, 2004 ; Kutz & Strassman, 1977 ; O’Sullivan et al, 2005 ). Most studies suggest negligible public health risks from exposure to adulticides; however, no study has quantitatively combined the results from risk assessment, epidemiology, and biomonitoring studies, and their seemingly disparate data metrics, to obtain an overall estimate of the risk.…”
Section: Case Studymentioning
confidence: 99%